Methodology for basic model development to assess the level of corporate social - Psareva, Nadezhda Yu. (Opción, 2019)
The purpose of this paper is to identify a set of factors characterizing the performance of modern corporations in terms of CSR. Expert evaluation method combined with graphics and mathematical methods is the method to analyze the issue. As a result, the combination of the indicators in each activity area can be changed, their quantitative and qualitative values can be changed depending on our understanding of CSR. In conclusion, transformation of different measurement units of indicators and their quantitative assessment into a score-based system help to include different indicators into the model and to have one measurement unit.